Simple and versatile long range swept source for optical coherence tomography applications. (27th October 2015) - Bräuer, Bastian; Lippok, Norman; Murdoch, Stuart G; Vanholsbeeck, Frédérique
Abstract: We present a versatile long coherence length swept-source laser design for optical coherence tomography applications. This design consists of a polygonal spinning mirror and an optical gain chip in a modified Littman–Metcalf cavity. A narrowband intra-cavity filter is implemented through multiple passes off a diffraction grating set at grazing incidence. The key advantage of this design is that it can be readily adapted to any wavelength regions for which broadband gain chips are available. We demonstrate this by implementing sources at 1650 nm, 1550 nm, 1310 nm and 1050 nm. In particular, we present a 1310 nm swept source laser with 24 mm coherence length, 95 nm optical bandwidth, 2 kHz maximum sweep frequency and 7.5 mW average output power. These parameters make it a suitable source for the imaging of biological samples.